ABOUT SOME APPROACHES OF THE MIGRATORY POLITICS OF THE STATES IN INTERNATIONAL LAW - Z.K.Ayupova,; D.U. Kussainov, (Academic Journal of Physical and Chemical Sciences, 2019)
Presently migration became one their factors of all global problems standing before humanity. Development of the world system requires the change of priorities and going near understanding of migration, to migratory politics of the states, assisting an achievement and maintenance of balance of interests of international subjects participating in adjusting of migratory processes. In itself migration is the same phenomenon, as well as right for the states to regulate the movements of persons through the borders of the states and carry out border control. Migration through the borders of the states is an international problem, as the not alone state participates in this process. On this basis, international migration is regulated by both international and national norms. Coming forward in the past mainly in the forms of nomads, soldiery and colonization migrations, international migration of population with development of the system of economic relations between the states purchased new lines. There was a necessity for the enormous moving of people. Millions of people abandoned native edges and directed in other countries in search of material sufficiency and releasing from inequality. Strengthening of tendency to the increase of migratory processes in the modern world, the necessity of international-legal permission and adjusting of different forms of migration of population affects expansion of international cooperation of the states in this sphere.